INVESTIGATION OF BLOOD FLOW ON THE INPUT OF AORTA - Nastenko, Eu. A. (Electronics and Control Systems, 2018)
The processes of blood flow in the aorta under the influence of swirling blood flow at the output from the left ventricle of the heart are studied. The problem of simulated swirling flow of blood in the left ventricle as a nonlinear boundary value problem in the form of a system of differential equations in partial derivatives with moving limits is formulated. Expressions for the field of blood flow velocity and pressure in the left ventricle are obtained. The flow of blood in the aorta under the influence of a swirling flow at the exit from the left ventricle is described by a system of nonlinear equations in partial derivatives. The solution of this boundary-value problem is sought using an iterative procedure based on using integral transformations for spatial variables and time.